RESPON PERTUMBUHAN TINGGI DAN PRODUKSI TANAMAN CENGKEH (Syzigium aromaticum L.) TERHADAP PEMBERIAN PACLOBUTRAZOL - Moningka, Frieda F.; Runtunuwu, Semuel D.; Paulus, Jeanne M. (EUGENIA, 2012)
ABSTRACT Â  This research aims to produce a shorter cloves and generate more interest and qualified by the presence of paclobutrazol treatment. The results showed that the high accretion paclobutrazol can produce the content of chlorophyll a (0,032 mg g-1) and chlorophyll b (0,004 mg g-1), dry weight of 1000 grains (207 g) and dry weight / plant (6.038 kg) was 8 years old clove higher than the control. Recommended further research to determine the maximum effect of paclobutrazol application on plants. Paclobutrazol at a dose of 2.5 g / tree height increment can deliver maximum results of cloves. KeywordsÂ  : Cloves, gibberallin, paclobutrazol